Chemical Activation of Natural Zeolite for Purification of Fish Oil from By- Product of Fishmeal Processing - Ahmadi, Kgs; Mushollaeni, Wahyu (Fakultas Teknologi Pertanian Universitas Brawijaya, 2007)
Omega-3 fatty acid has health benefits. Â Indonesia has some species of fish that contain this kind of fatty acid such as lemuru. Â However its utilization as ï·-3 fatty acid source is still limited. Â Fish oil from lemuru meal processing has poor quality because of its color and peroxide value, besides its free fatty acid content. Therefore purification process should be employed to improve its quality.This research was conducted to elucidate the performance of natural zeolite in purification of fish oil from lemuru meal processing. Acitivation of natural zeolite was employed to increase its adsorption capacity. Â One Â technique to activate natrural zeolite was chemical activation by strong acid (HF, H2SO4, dan HCl). Concentration level of activated zeolite in purification was also defined.Â The best result was natural zeolite activated by HCl and concentration level of 15%. Â The characteristics of purified lemuru oil were as followed: absorbance at 430 nm of 0,24, free fatty acid content 4,12, Ï‰-3 fatty acid content of 20,34%, and peroxide value of 93,6 meq/kg.Keywords: natural zeolite, purification, lemuru meal processing, fish oil